Hakikat Metodologi Studi Islam - Nurillaida; Nurul Fadhilla; Shanaya Agiaska Valeri; Tantri Dea Ninda; Virna Nuraini (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Methodology is a fundamental concept in scientific studies that plays a crucial role in guiding the systematic pursuit of truth. Etymologically, the term derives from Greek: metha (behind), hodos (path), and logos (science), which collectively refer to the science of methods or ways used to achieve specific goals. In the context of knowledge, methodology functions as a framework that organizes logical steps in research or academic inquiry. The Kamus Umum Bahasa Indonesia defines methodology as the science of methods used in education and other scientific disciplines, while method itself is described as a well-thought-out and organized way to reach a research objective. Louay Safi strengthens this understanding by stating that methodology is a scientific discipline that discusses and justifies the use of scientific procedures in examining natural and social phenomena. Therefore, methodology is not merely a set of techniques but also involves an epistemological foundation for structuring scientific approaches. A deep understanding of methodology is essential to producing valid, measurable, and accountable research across both natural and social sciences.